Lithospermum erythrorhizon extract alleviates immunosuppression via MAPK signaling pathway - Chi, Xiaoqing; Ping, Li; Gai, Renhua; Weng, Qinjie (Frontiers in Veterinary Science, 2025)
IntroductionLithospermum erythrorhizon extract (LEE), rich in shikonin and its derivatives, has been traditionally valued for anti-inflammatory and wound-healing properties.ObjectiveThis study aimed to investigate the immunoprotective effects and underlying mechanisms of LEE in a rat model of dexamethasone-induced immunosuppression.MethodsOne hundred SPF Sprague–Dawley rats were randomized into control, model, and LEE treatment groups (10, 20, 40 mg/kg). Immunosuppression was induced with dexamethasone (7.5 mg/kg, i.p.) for 7 days, followed by oral LEE for 21 days. Body weight, food consumption, hematology, and serum biochemistry were assessed. Immunomodulatory effects were evaluated via cytokine profiles, immunoglobulin and complement levels, lymphocyte subtypes and proliferation, immune organ indices, and histopathology. Potential targets and pathways were predicted by network pharmacology and validated by RT-qPCR.ResultsLEE significantly improved body weight, white blood cell counts (WBC), lymphocyte (LYMPH%), and CD4+/CD8+ ratio. It downregulated pro-inflammatory cytokines (tumor necrosis factor-α, interleukin-1β, interleukin-6) (TNF-α, IL-1β, IL-6) and upregulated anti-inflammatory cytokine interleukin-4 (IL-4), while restoring immunoglobulin G, M and A (IgG, IgM, IgA) and complement 3 and 4 (C3, C4) levels. LEE also enhanced ConA- and LPS-induced lymphocyte proliferation, and alleviated spleen and thymus atrophy, as evidenced by increased organ indices and improved histopathology. Network pharmacology highlighted MAPK signaling, particularly the p38 and JNK- as central pathways, which was supported by RT-qPCR showing upregulation of Akt1, Mapk3, Mapk14, Pik3ca, and Mapk1.ConclusionLEE effectively ameliorates dexamethasone-induced immunosuppression by restoring immune cell activity, regulating cytokine balance, and preserving immune organ structure, primarily via MAPK pathway regulation. This study provides a scientific basis for the development of LEE as a natural immunomodulatory agent in managing immunosuppression in mammals.